Fox 8 : a story - Saunders, George, 1958- (Random House, 2018)
Idealistic Fox 8's ability to communicate in "Yuman" cannot save his pack when their den and food supply are destroyed to build a mall, so he writes a letter asking for an explanation of human's cruelty.